Pengaruh Pemanfaatan Teknologi Informasi terhadap Ketepatan Waktu Pelaporan Keuangan pada SKPD Kabupaten Toraja Utara - Soladisa Madeten; Agustinus Mantong (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2025)
This study aims to determine the effect of information technology utilization on the timeliness of financial reporting in the Regional Apparatus Work Units (SKPD) of North Toraja Regency. The use of information technology is expected to enhance the effectiveness and efficiency of the financial reporting process so that reports can be prepared and submitted on time. However, variations in reporting timeliness among several SKPDs indicate the need for further examination of the extent to which information technology has been optimally utilized. The research method employed is a quantitative approach with a simple linear regression analysis technique. Data were collected through questionnaires distributed to financial staff of SKPDs in North Toraja Regency, with a total of 50 respondents. Data analysis was conducted using SPSS through validity testing, reliability testing, classical assumption testing, and hypothesis testing. The results of the study show that the utilization of information technology has a positive and significant effect on the timeliness of financial reporting. These findings highlight the importance of optimizing the use of information technology in supporting effective and timely financial reporting.